THE EFFECT OF THE OPENING ANGLE OF FURROW OPENER WINGS WITH UNEQUAL WING ASSEMBLIES ON ITS PERFORMANCE INDICATORS - Imomqulov Qutbiddin Boqijonovich; Muydinov Umid Maxkamovich; Mamadaliyeva Gulxayo Qutbitdin qizi (Modern American Journals, 2025)
This article presents experimental methods for determining the opening angles of a furrow opener with unequal wing assemblies, which is part of a combined machine designed to apply organic fertilizers uniformly in orchards while simultaneously opening irrigation furrows.
Keywords: Moldboard plow, disc plow, opening angle, draft resistance, furrow depth, wing assemblies, machine, soil ridge height.